The tourist map, scientific tool that supports the exploration of protected areas, Bihor County, Romania - Grigore Vasile HERMAN; Dorina Camelia ILIEȘ; Ștefan BAIAS; Miron Florin MĂDUȚA; Alexandru ILIEȘ; Jan A. WENDT; Ioana JOSAN (Editura Universităţii din Oradea, 2016)
The study area is a Nature 2000 protected site from Bihor County, Romania. The present study aims at identifying the opportunities for the implementation of a bioeconomic exploitation system, by tourism development, according to its necessities for conservation and protection of cultural and natural elements. The landscape value is assessed, using different available thematic layers, using a combination of GIS and graphics. The resulting visibility of the tourist map of natural and anthropic values can be a very useful tool for tourists, the conservational custodian of the Nature 2000 site, local public administration for tourism development and leisure activities, participative touristic planning etc.